From clouds to hailstorms: a policy and administrative science perspective on safeguarding public values in networked infrastructures. (13th May 2009) - Veeneman, Wijnand; Dicke, Willemijn; De Bruijne, Mark
This paper analyses how public values are achieved in Dutch infrastructures and distinguishes four crucial stages in decision making processes: the advocacy process, the political process, the bureaucratic process and the provision process. An important conclusion of this paper is that the character of public values undergoes significant changes in each of these stages of the decision-making process, generally from more abstract notions to more concrete. With the level of abstraction, the content of the public value also tends to shift from stage to stage. We conclude that a balanced repertoire of safeguarding mechanisms should address the various stages.